2004
DOI: 10.1038/nm1004
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of an orthologous model of autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a leading cause of end-stage renal disease. The vasopressin V2 receptor (VPV2R) antagonist OPC31260 has been effective in two animal models of PKD with pathologies that are probably related. Here we show, in a mouse model of ADPKD (Pkd2(-/tm1Som)), a similar cellular phenotype and response to OPC31260 treatment, with reduction of renal cyclic AMP (cAMP) levels, prevention of renal enlargement, marked inhibition of cystogenesis and protection of renal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
320
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(344 citation statements)
references
References 12 publications
15
320
1
8
Order By: Relevance
“…Recent reports have shown that the same chemical molecule (a vasopressin V2 receptor antagonist, OPC31260) can inhibit cyst progression in both a rat genetic model of ARPKD and a mouse genetic model of ADPKD, suggesting that both causal gene products for AD-PKD and ARPKD may reside in a common molecular pathway. 42 Recently, our company study demonstrated that FPC and PC2 indirectly interact via their COOH-termini and that this is mediated by KIF3B, a motor subunit of the heterotrimer kinesin-2. 36 Pkd2-channel activities were significantly altered when the FPC-PC2 complex was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that the same chemical molecule (a vasopressin V2 receptor antagonist, OPC31260) can inhibit cyst progression in both a rat genetic model of ARPKD and a mouse genetic model of ADPKD, suggesting that both causal gene products for AD-PKD and ARPKD may reside in a common molecular pathway. 42 Recently, our company study demonstrated that FPC and PC2 indirectly interact via their COOH-termini and that this is mediated by KIF3B, a motor subunit of the heterotrimer kinesin-2. 36 Pkd2-channel activities were significantly altered when the FPC-PC2 complex was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Mozavaptan is a selective vasopressin-2 receptor antagonist that decreases renal cAMP levels and attenuates cyst growth. 17 qPCR analysis revealed that the expression of primiR-21 was reduced by approximately 30% (P=0.03) and that the expression of mature miR-21 transcripts was reduced by 50% (P=0.01) in kidneys of mozavaptan-treated Pkd2 2/WS25 mice compared with vehicle-treated Pkd2 2/WS25 mice ( Figure 2, I and J). Consistent with the notion that cAMP signaling regulates miR-21 independent of its host gene Vmp1, mozavaptan treatment did not affect Vmp1 expression.…”
Section: Mir-21 Is Upregulated In Pkdmentioning
confidence: 99%
“…However, if we assume that the primary defect in type 2 ADPKD is PKD2-mediated Ca 2+ influx (and not Na + or K + which also pass through PKD2), it is possible that a connection between a Ca 2+ channel and cAMP can be made. It has been reported that cystic cells have abnormally high levels of cAMP [79][80][81][82] and the administration of a vasopressin V2 receptor antagonist, which reduced cAMP, suppressed the cystic phenotype in PKD2 knock out mice [83] and other animal models [84,85]. It is also known that store-operated Ca 2+ channels are directly coupled to specific isoforms of adenylyl cyclases [86][87][88].…”
Section: Pkd2-mediated Signal Transductionmentioning
confidence: 99%